Peran dan Fungsi Manajemen Sumber Daya Manusia - Wiguna, Wahyu; Dwi Cahya Oktavian; Muh. Rahmat Padli; Maria Marice Klau; Ami Apriana; Rauda Tunyanan (Journal of Management and Bussines (JOMB), 2026)
This study aims to analyze the role and function of Human Resource Management (HRM) in improving organizational effectiveness and productivity and supporting the sustainable achievement of company goals. The research method used is a qualitative approach with library research. Data was collected from books, scientific journals, and relevant literature. Data were then analyzed using descriptive-qualitative techniques through the stages of data reduction, data presentation, interpretation, and conclusion drawing. The results indicate that HRM plays a strategic role in workforce planning, recruitment and selection, training and development, compensation, industrial relations management, and employee welfare. Furthermore, HRM functions encompass managerial, operational, and strategic functions that are integrated to ensure the availability of competent, adaptive, and productive human resources in facing the dynamics of the organizational environment. The conclusion of this study confirms that effective and systematic human resource management is a key factor in organizational success because people are the primary asset that determines the achievement of a company's short-term and long-term goals.   Keywords: Human Resource Management, Work Productivity, Organization